Separation of Branched and Isoprenoid Glycerol Dialkyl Glycerol Tetraether (GDGT) Isomers in Peat Soils and Marine Sediments Using Reverse Phase Chromatography - Rattray, Jayne E.; Smittenberg, Rienk H. (Frontiers in Marine Science, 2020)
Glycerol dialkyl glycerol tetraethers (GDGTs) have become one of the most investigated lipid classes in marine and terrestrial organic geochemical research. GDGTs are microbial membrane core lipids biosynthesized as multiple homologue series of isoprenoid or methyl-branched isomers whose relative abundance depend on a range of environmental parameters, including temperature. This has led to the development of GDGT-based temperature proxies. Critical for GDGT analysis and the further development of their use as environmental proxies is a good chromatographic separation of the full range of structural and stereo-isomers with potential for discovery of novel GDGT variants. Several HPLC methods have been developed to this extent, but partial co-elution of GDGTs remains an issue despite long run times. In this study, we investigate the effects of different types of reverse phase (RP) chromatography on the separation of GDGT isomers. The RP method presented here gives good separation of isoGDGT isomers in comparison to the recently developed double column HILIC analysis operated in normal phase (NP) and has a shorter run time. In marine samples, the regularly reported isoprenoid GDGTs separated in a similar way as in NP, however an earlier eluting group was observed to elute with the crenarchaeol isomer used in the TEX86 proxy. In a Swedish peat bog sample, a large range of isoGDGT isomers were observed. and for branched GDGTs, near baseline separation of the 5- and 6-methyl branched GDGT isomers was achieved, as well as asymmetric isomers like the 5/6 isomer. The C18-XB method is rapid and versatile and can be set up on either low-pressure HPLC systems (max 400 bar) with a sample run time of 25 minutes for brGDGTs and 45 minutes to include isoGDGTs. On UHPLC-MS systems (> 600 bar) the sample run time is reduced to 15 minutes. Both methods meet the demands of high-resolution sampling in shorter time and for low running costs. The C18-XB RP method presented here gives unusual separation of branched GDGTs and could be a useful tool for the further elucidation of the biological sources and environmental factors that play a role in the production of different GDGT isomers.